Technology, innovation, and firm competitiveness: Firm level analysis in Cambodia - Hing Vutha; Shandre Mugan Thangavelu; Ratha Kong (Asian Development Bank Institute (ADBI), 2023)
The paper examines the innovation and competitiveness of firms, especially with regard to the channels of technology transfer and the nature of innovation activities that influence firm performance in the Cambodian economy. Despite the growing importance of innovation, there has been no empirical analysis of the factors affecting technological and innovative development and the impact that these factors have on firms' productivity in Cambodia. We use the World Bank Enterprise Survey (WBES) for Cambodian enterprises for our empirical implementation. The results of the research indicate that overseas linkages that include both upstream and downstream activities could affect productivity growth at both firm and industry levels. We also find that technology and innovation have a positive impact on the productivity of firms in Cambodia.
Keywords: D240; 330; technology; innovation; productivity; human capital; export and import